Penerapan Diversifikasi Snack Makaroni Ikan Aneka Rasa sebagai Upaya Akselerasi Daya Saing Produk Lokal Kelompok Mastali Madu - Sidauruk, Santhy W.; Dewita, Dewita; Sari, N. Ira; Desmelati, Desmelati; Yanti, Chicka Willy; Metalisa, Rindi; Huda, Nurul; Fatiranes, Erlando; Putri, Tiara Beneva; Sadewa, Bagaspati L.; Fanzuri, M. Reza (Unri Conference Series: Community Engagement, 2025)
The Mastali Madu group is confronted with significant challenges in the marketing of its fish macaroni snacks. These challenges primarily stem from the group’s limited product variety in terms of flavor options and the absence of distribution permits, which restricts its marketing opportunities. To address these issues, a community service activity was conducted in the form of diversifying fish macaroni snacks into various flavors, with the aim of accelerating the competitiveness of the Mastali Madu group’s local products. The implementation methods included assistance in the diversification of fish macaroni snacks with various flavors and the procurement of product distribution permits. The findings of the activity demonstrated an enhancement and the capacity in the group members’ to manufacture fish macaroni snacks with diverse flavors, including grilled corn, BBQ, and balado. These snacks were found to possess a palatable taste, a crispy texture, and 86.67% extremely like of panelists’ hedonic level. From an economic perspective, the product has demonstrated added value in comparison to previous iterations, offering a diverse range of flavors and holding a-P-IRT license, thereby facilitating market expansion. The conclusion of this activity is that the implementation of diversified fish-flavored macaroni snacks can serve as one strategy to accelerate the competitiveness of local products, while also enhancing skills, self-reliance, and business opportunities for the Mastali Madu Group.